The landscape of antimicrobial resistance in the neonatal and multi-host pathogen group B Streptococcus: review from a One Health perspective - Oliveira, Laura M. A.; Simões, Leandro C.; Costa, Natalia S.; Zadoks, Ruth N.; Pinto, Tatiana C. A. (Frontiers in Microbiology, 2022)
Group B Streptococcus (GBS) stands out as a major agent of pediatric disease in humans, being responsible for 392,000 invasive disease cases and 91,000 deaths in infants each year across the world. Moreover, GBS, also known as Streptococcus agalactiae, is an important agent of infections in animal hosts, notably cattle and fish. GBS population structure is composed of multiple clades that differ in virulence, antimicrobial resistance (AMR), and niche adaptation; however, there is growing evidence of interspecies transmission, both from evolutionary analysis and from disease investigations. The prevention of GBS infections through vaccination is desirable in humans as well as animals because it reduces the burden of GBS disease and reduces our reliance on antimicrobials, and the risk of adverse reactions or selection for AMR. In this perspective article, we navigate through the landscape of AMR in the pediatric and multi-host pathogen GBS under the One Health perspective and discuss the use of antimicrobials to control GBS disease, the evolution of AMR in the GBS population, and the future perspectives of resistant GBS infections in the post-pandemic era.